The travelers - Porter, Regina (London: Vintage, 2020)
Illuminating more than six decades of sweeping change - from the struggle for civil rights and the chaos of Vietnam to Obama's first year as President - James and Agnes's families will come together in unexpected, intimate and profoundly human ways.